Long-Term Integration Planning Scheme for Superior Product Management for Economic Competitiveness of Fakfak Regency - Zannat Zannat; Sri Rahayu; Titis Istiqomah; Roy Sumaryono (RTTM, 2024)
The management of superior products for economic competitiveness is needed to increase potential products developed in a region by utilizing natural resources and local human resources that are market-oriented and environmentally friendly so that they have a competitive advantage and are ready to face global competition. The research aims to find out the long-term integration planning of superior product management for the economic competitiveness of Fakfak district. The research was carried out during September – October 2023. Descriptive research method with a combination of quantitative and qualitative analysis approaches. Data was obtained through a direct survey of respondents who had been deliberately determined. The data obtained are given a weight value based on the assessment indicators obtained from the results of the preliminary research. The validity and reliability of the data were tested gradually and in a structured manner using the triangulation and role sharing approaches. The results of the study are presented in the form of a spider web diagram equipped with an illustration of the shift share gap value, and a regression equation model obtained from the SPSS statistical device version 2.3.